2021
DOI: 10.1002/vro2.2
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of probiotic effects on gastrointestinal signs in dogs with multicentric lymphoma undergoing multi‐agent chemotherapy: A randomised, placebo‐controlled study

Abstract: Background Gastrointestinal (GI) toxicity is a major dose‐limiting factor in dogs undergoing chemotherapy. A proposed mechanism of GI toxicity includes chemotherapy‐driven GI dysbiosis. This study was designed to determine the effects of probiotic administration on GI side‐effects in dogs receiving multi‐agent chemotherapy. Methods Ten client‐owned dogs with multicentric lymphoma were enrolled in a prospective, randomised, placebo‐controlled single‐blinded study. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In another study, its use did not reduce the frequency of gastrointestinal AE in dogs receiving vincristine or cyclophosphamide 47 . Moreover, effects of prophylactic probiotics on gastrointestinal AE were investigated in one study, and there were no significant decrease of the number of episodes of diarrhoea 79 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, its use did not reduce the frequency of gastrointestinal AE in dogs receiving vincristine or cyclophosphamide 47 . Moreover, effects of prophylactic probiotics on gastrointestinal AE were investigated in one study, and there were no significant decrease of the number of episodes of diarrhoea 79 …”
Section: Discussionmentioning
confidence: 98%
“…47 Moreover, effects of prophylactic probiotics on gastrointestinal AE were investigated in one study, and there were no significant decrease of the number of episodes of diarrhoea. 79 Type of antineoplastic agents used during chemotherapy could impact occurrence and severity of AE. As previously quoted, one study reported an independently increased risk of febrile neutropenia with vincristine and doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…The overall composition of the fecal microbiome of dogs with multi-centric lymphoma treated with CHOP chemotherapy was significantly different than clinically normal dogs before and during treatment. This is consistent with previous literature showing altered fecal microbiomes in dogs with multi-centric lymphoma at diagnosis 72,86 and during treatment 86 . Within our treatment population, a statistically significant difference was not detected in α-diversity or β-diversity over time.…”
Section: Chapter 4: Discussionsupporting
confidence: 93%
“…Finally, a recent prospective placebo-controlled study investigated the use of probiotics in dogs receiving multi-agent chemotherapy for multi-centric lymphoma 86 .…”
Section: The Microbiome In Veterinary Medicinementioning
confidence: 99%
“…Although probiotics were associated with no complications in small studies of dogs with parvoviral enteritis or lymphoma undergoing chemotherapy, 33 , 53 their use has been episodically associated with opportunistic fungemia and bacteremia in immunosuppressed or critically ill people. 46 , 54 , 55 It is unclear whether glucocorticoid‐induced immunosuppression, particularly when administered as part of multimodal immunosuppression which already increases the risk of opportunistic infection, 56 , 57 poses the same risk.…”
Section: Discussionmentioning
confidence: 99%